Assessment of load carrying capacity enhancement of an open spandrel masonry arch bridge by dynamic load testing. Issue 8 (17th November 2017) - Ataei, Shervan; Miri, Amin; Jahangiri, Meysam
ABSTRACT: Health monitoring of masonry railway bridges is vital due to their long life in service, an increasing demand for higher axle loads, and the recent trends in sustainability that requires the preservation of aged masonry bridges. Safety assessment of a 70-year-old masonry arch bridge is presented. The bridge is situated in a S-shaped curved section of the track and has long spans of 36 m. Added the deterioration of masonry due to old age of the bridge and complex behavior of masonry arch bridges, dynamic load tests are employed and global structural responses to allowable loading schemes of the bridge are determined. Dynamic amplification factors are determined and compared to those proposed by standards and it is concluded that experimental values are higher than those proposed by standards. Model calibration is carried out using deflection signatures. Experimental and analytical natural frequencies are compared for model verification. Having the model calibrated and verified, safety of bridge in serviceability and ultimate limit states due to application of operational loading schemes and higher axle loads are assessed. It is concluded that the bridge is safe regarding operational loading patterns, and could withstand an increased axle load of 25 tons.